The Correlation Between Digital CRM System Features and Performance of Service in Clinics: A Case Study of the Fook Kang Clinic. - Bingyang, Wu; Chaiwiwat, Uswin; Wongkumchai, Tachakorn (Academic Journal of Local Development, 2025)
This study investigates the impact of digital customer relationship management (CRM) systems on clinic service performance, using Fukang Clinic as a case study. The objective is to determine which CRM system features most significantly influence service outcomes and to evaluate their relative importance. With the increasing reliance on digital tools in healthcare, CRM systems play a crucial role in optimizing workflow, improving patient experience, and strengthening competitive advantages. However, many clinics face challenges in CRM adoption, including integration with existing systems, privacy concerns, and staff adaptation. The research method used a quantitative descriptive survey, taking 155 clinic staff as a sample, covering different professions such as doctors and nurses, and collecting data through a structured questionnaire. Analyze data using descriptive statistics, correlation, and regression techniques to determine the relationship between CRM functionality and service outcomes. Key findings demonstrate a positive relationship between a user-friendly CRM interface, strong integration capabilities, and enhanced service quality, resulting in improved workflow efficiency and patient retention. The study provides practical insights for clinics adopting CRM systems, highlighting strategies for implementation, system customization, and training. It concludes by recommending further research on AI integration, patient perspectives, and comparative studies across different healthcare settings.